1992
DOI: 10.1126/science.257.5067.225
|View full text |Cite
|
Sign up to set email alerts
|

Phototaxis of Spiral Waves

Abstract: The drift of spiral waves toward regions of higher light intensity was observed experimentally in the ruthenium-catalyzed Belousov-Zhabotinsky reaction. A light gradient can thus be used to manipulate optical information in new computational systems based on photochemical media. The drift of a gradient that is rotationally invariant in space is three to four times as fast as that of a translationally invariant gradient. Simulations based on the use of a cellular automaton, which is made isotropic by a semirand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…Temporal resonance [6], drift of vortices due to parameter gradients [7,8] or external fields [9], and anchoring on localized defects [10] are among the most studied effects.…”
mentioning
confidence: 99%
“…Temporal resonance [6], drift of vortices due to parameter gradients [7,8] or external fields [9], and anchoring on localized defects [10] are among the most studied effects.…”
mentioning
confidence: 99%
“…The travelling and spiral waves here show a similar behaviour to waves in prebiotic evolution 6 , in host-parasitoid systems 7 , as well as in excitable media (see Refs 4,[8][9][10] and references therein) such as chemical reactions, heart muscle and epidemics. In the latter, the black, dashed and white regions shown in Fig 3b, correspond to excited, refractory (or immune) and excitable (or resting) states, respectively.…”
Section: Resulting Modesmentioning
confidence: 69%
“…Quite recently, it was found that light induces oscillations in the H 2 O 2-Fe(CN) 6 4-system in a continuously stirred tank reactor (CSTR). 8,9 As far as Ru(II)-catalyzed BZ systems are concerned, light works both as an inhibitor and promotor of temporal 4,[10][11][12][13][14][15][16] and spatial [17][18][19][20][21][22] oscillations. The work dealing with the influence of light on the Ru(II)-catalyzed BZ systems can be divided into two groups.…”
Section: Introductionmentioning
confidence: 99%